Problematics of Citizenship Education and Challenges for Teacher - Wahida Suaiba Lubis (International Journal of Students Education, 2024)
Objective study this for know problem in education citizenship at school base And What challenge the for a teacher and study this also aim for discuss in a way deep about constraint which faced teacher citizenship in participant educate in school. Approach which used in this research is a qualitative approach and changing the curriculum is a challenge very in worried on moment this wrong the only one student more tend own or get competence cognitive. In matter this challenge for teacher citizenship facing a curriculum whose direction is not only to provide knowledge but also to teach method think education Pancasila and citizenship own interest for translate think level tall in process his learning because, wrong one the aim of Pancasila and citizenship education is to form a personality think critical is element important in personality that and problematic which faced in implementing methods in providing easy project tasks to students so that, in implementation, students do not experience obstacles due to project assignments is task which futures. Problematic which faced teacher is time implementation in the assessment of PPKN subjects.